Sobre a pele do discurso, a tatuagem da língua : a intertextualidade de Stricto sensu temática e explícita - Dal'ponte, Wilian (2013)
During the production of this report, we propose to analyze, due to its representativeness to the linguistics studies, the method of intertextuality s manifestation stricto sensu themes and explicit in three texts, both belonging to the speech gender. Those prototypes written were produced by diferente periods of Brazil s history: the Colonial, the Imperial, and the Contemporary. Our main goal is to show what was stipulated to be named as intertextuality, focusing, mainly, the typology stricto sensu themed and explicit. From this, we will try to answer some fundamental questions to the search, which has descriptive nature, bibliographic and qualitative: Is it possible - after a long period of investigations - to define, exactly, what is intertextuality? May it be a stable concept that regards its characterization? Is it an indefinite textual constituting waiting from definitive arremates that are capable to ensure its conceptual stability? What are the meanders whereby it establishes itself in the speech? To the development of this task, we adopted as main theorical reference the titles of Kristeva (1974), Paulino (2005), Koch (2007) e Samoyault (2008). Willing that the proposed goal was achieved, we did, after the selection of the corpus, the analysis in two stages: 1) simulcast presentation, to the reader, of the intertextual fragments of the three speech, putting them in the discussion spot saving to each one of the two typologies inherent to Intertextuality strict sensu and 2) analysis - complemented by explanation theoretical-reflexive - pavement on the postulates of the said writers and the other theorical we may judge useful to the realization of this task. Through this study, then, we noticed that the intertextuality is one, besides other, constructive element of the texts, revealing itself through the diferente typological facets